Identifying the Semiotic Meaning of Li Bai's Poetry to Support the Learning of Chinese Literature Courses - Ainul Hanifah, Nur; Eza Febrian Putri, Amira; Syafruddin, Duddy; Olivia Firdaus, Dhevy (Nexus Publishing NXP, 2025)
This study aims to describe the sign system in the form of icons, indexes, and symbols in three poems by Li Bai entitled 玉阶怨 [yù jiē yuan] ‘Fretting on the Jade Staircase’, 怨情 [yuàn qíng] ‘Revenge’, and下江陵 [xià jiānglíng ‘down to Jiangling’. This research uses qualitative method and Peirce's semiotic analysis approach in the form of analytical description. The data sources in this study are three poetry texts contained in the book Tangshi Yibai Shou. The data were collected using reading and note-taking techniques. From the analysis, it can be seen that there is a whole system of signs, especially indexes and symbols that represent life in the Tang dynasty. This proves the existence of signs and relationships to the objects they represent. The relationship is in the form of similarity, convention, and existence to the object. The poems contain themes of longing, separation, sadness, and reflections on the relationship between humans and nature that represent life during the Tang dynasty. Semiotics in this study not only helps in interpreting Li Bai's poems, but also serves as a learning tool in Chinese literature courses. Through understanding the meanings in the poems, students can learn more about the culture and historical background that influenced the birth of these literary works.